Effectiveness Of Healthy Food Education On Motivation And Attitude Of Mothers In Preventing The Risk Of Stunting - Aulia, Tiara Adinda; Amalia, Fierdina; Sureskiarti, Enok; Dirdjo, Maridi Mirsan (Open Access Health Scientific Journal, 2025)
Background: Stunting is a health problem caused by chronic malnutrition in children, which affects cognitive and motor growth and development. The role of mothers is very important in preventing stunting, especially through a good understanding of nutritional intake. Education is one of the effective efforts in increasing mothers' motivation and attitudes in providing healthy food to children. This study aimed to evaluate the Effectiveness Of Healthy Food Education On Motivation And Attitude Of Mothers In Preventing The Risk Of Stunting.Methods: This study used a Quasi-Experimental design with a pre-test and post-test with control group design. The sample consisted of 60 mothers who had toddlers at the Kelapa Gading Sehat Posyandu (animation video group) and the Amalia Posyandu (booklet group), each consisting of 30 people. Data were collected using a questionnaire and analyzed using a paired t-test and an independent t-test to see the effectiveness of the educational intervention.Results: The results showed a significant increase in mothers' motivation and attitudes after being given education. In the animated video group, the average motivation score increased from 35.8 to 48.9, while in the booklet group it increased from 36.4 to 49.8 (p-value = 0.000). For attitude changes, the animated video group increased from 39.27 to 45.10, while the booklet group increased from 38.03 to 43.93 (p-value = 0.000). However, no significant difference was found in the improvement of attitudes between the two groups (p-value = 0.053).Conclusion: This study concludes that nutrition education based on animated video media and booklets can be an effective method in increasing mothers' motivation and attitudes in efforts to prevent stunting.